Development of Green Economy-based Ecotourism Packages in Proklim Merbabu Asih Village, Cirebon City - Shabrina, Fitriatunnisa; Mustafa, Iva Yulia (Ann Publisher, 2025)
Background. Sustainable tourism development is an essential strategy in improving people's welfare while preserving the environment. ProKlim Village RW 08 Merbabu Asih, Cirebon City, is one of the community-based areas with great potential to be developed into an educational ecotourism destination. However, the increase in tourist visits has not been offset by the availability of structured and sustainable tour packages. Aims. This research aims to develop a green economy-based ecotourism package that is integrated with the local environmental, social, and economic potential in ProKlim Merbabu Asih Village. Method. The research method used is a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and literature reviews. The research informants were selected using purposive and snowball sampling techniques, involving ProKlim village managers, local communities, the government, and academics. Conclusion. The results of the study show that the development of ecotourism packages is carried out through the stages of market research, destination determination, contract making, cost calculation, brochure preparation, and determination of tourism travel flows that refer to green economy indicators, namely emission and pollution reduction, environmentally friendly job creation, financial and ecological sustainability, and biodiversity conservation. This research produces several alternative tour packages, including daily, overnight, and incentive packages for domestic and international markets. Implications. The development of this green economy-based ecotourism package is expected to increase the economic value of the local community, strengthen the identity of ProKlim village as an environmental education tourism destination, and support sustainable tourism development in Cirebon City.